Pengaruh Perbandingan Konstruksi Stator Terhadap Tegangan Keluaran Generator Linier - Himawan, Muh Azis, Hasyim Asy'ari, ST.MT (2016)
The conditions with much of the island is a condition that becomes a unique problem and electricity equalization supply challenges for PLN. Therefore it is needed the enhancement in the power system that is more practical, efficient, and easy to maintenance and can be used for remote islands in Indonesia. Generator is a machine that is driven mechanically by the prime movers eg steam turbines, hydraulic turbines or diesel engines and produce energy to power lights or other machines. This study aimed to compare the stator design of radial type and linear-type. Furthermore, It is also addresses the manufacture of generators liner and also do comparison of three different pieces of stator winding amount, the air gap, as well as design. This study used different types of windings, namely winding diameter of 0.8 and 0.4 mm. In the stator 1 using coil diameter of 0.8 with the number of windings 70 windings, then resulted output voltage of 160 mV at a speed of 200 rpm. Then at 450 rpm produces a maximum voltage of 550 mV. In the stator windings to 2 using 0.4 in diameter by the number of coil windings 200, then produced 134 mV voltage pda speed of 200 rpm. Then, at a speed of 450 rpm produces 560 mV. In the stator windings using 0.4 to 3 mm by the number of coil windings 200, can produce output voltage of 2 V at a speed of 200 rpm. Then, at a speed of 500 rpm to produce a 3.3 V output voltage.